REKONSTRUKSI PERTAHANAN JEPANG TERHADAP KONTINGENSI KAWASAN ASIA TIMUR - Aditya Prabowo; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
One of the main challenges in Japan's defense is the risk of a security dilemma due to the contingency that occurs in the East Asia Region, because each country needs to take action for reasons that have a defensive motive, including Japan. The increasingly challenging security environment of the East Asia Region has brought about drastic changes for Japan recently with its defense rebuilding efforts and Japan's national security policy. By maintaining its basic stance as a peace-loving country, Japan is expected to play a more active role in regional security. In this study, the authors used library research methods and qualitative research. The analysis in this study uses a nation-state level analysis, using the concept of the Security Dilemma, within the framework of the deterrence theory. The perspective in this study uses the perspective of structural realism—neorealism. The findings show that Japan's current foreign policy of adopting Detterence can be reconstructed towards Extended detterence and will continue to develop as Japan's reaction to the contingency that occurs in East Asia and the role of the growing Japan-US alliance is. With a rebuild defense that complies with Japan's constitutional limitations as well as increasing Japan's offensive capabilities, will help Japan contribute more to peace and deterrence in the East Asia Region. Keyword(s): Japan Defenses, Contingency, Detterence Theory